Transcriptional activation by the papillomavirus E6 zinc finger oncoprotein. - Lamberti, C (1990)
The introduction of the bovine (BPV) or human papillomavirus E6 gene into susceptible cells can result in their transformation, but there are few clues to the mechanism of action of the E6 gene. The characteristic features of E6 proteins are their small size (approximately 150 amino acids) and the potential to form two large zinc fingers. To determine if E6 can function as a transcription factor, the BPV E6 gene was fused to the sequence specific DNA binding peptide encoded by the BPV E2 gene. This chimeric E6-E2 protein trans-activated promoters that incorporated E2 binding elements in both rodent cells and Saccharomyces cerevisiae. In the absence of E6-E2 localization to the target promoter, trans-activation did not occur. Alteration of the cysteine residues at the base of each finger abrogated the transcriptional activity of the E6-E2 hybrids. These data demonstrated that the BPV E6 gene encodes a transcription activation domain and imply that a specific structure of the protein, most likely the zinc fingers, is critical for this function. Since these cysteine mutants are also transformation defective, E6 transcriptional functions may be required for its oncogenic activity.